Evaluation of The Implementation of The Development of The State Civil Apparatus (Case Study on The Implementation of Transfers and Promotion of The State Civil Apparatus in Bulukumba Regency) - Andi Meuthia Matalatta; Muh. Akmal Ibrahim; Muhammad Yunus (Enrichment : Journal of Management, 2021)
The development of state civil servants in cases of mutation and promotion is an activity directed at increasing the capacity and competence of employees so that they can have good mental and moral attitudes and increase skills, skills and expertise in order to support employee performance. evaluation of the implementation of the development of the State Civil Apparatus in the Mutation and Promotion case study in Bulukumba Regency. The approach used is qualitative, data obtained through direct field observations, interviews and document analysis. Data analysis used is data reduction, data presentation, and drawing conclusions. The results show that the evaluation of the implementation of the development of the state civil apparatus, case studies of the implementation of transfers and promotions, such as (a) the effectiveness can be the result of employee development in accordance with the objectives of the transfer and promotion (b) the efficiency can assess how much effort is needed in developing the civil apparatus State to achieve effective results in the implementation of transfers and promotions (c) Adequacy in the development of the state civil apparatus seen from how far the level of effectiveness satisfies employees in the implementation of transfers and promotions (d) The alignment is fair to employees from policies or regulations from the implementation of transfers and promotions e) Responsiveness of employees in fostering the state civil apparatus in the implementation of transfers and promotions (f) Determination seen from the program implemented in the development of employees where the program or policy can be a solution in the implementation of transfers and promotions. Factors that influence the implementation of the development of the state civil apparatus in cases of mutation and promotion (a) Nepotism system (b) Spoil system should employees who will be transferred and promoted to avoid political factors so that the implementation of promotion of employees goes according to the established procedure. Keywords : Evaluation, Development of State Civil Apparatus, Implemnetation of Transfer and Promotions